Revitalisasi Nilai Ukhuwah Islamiyah dalam Pendidikan Islam di Era Modernisasi Indonesia: Perspektif Pemikiran Ulama Nusantara - Rizki Maulana; Fadhila Najah Annisa; Adinda Sabrina Salsabila; Muhammad Syafiurrahman; Abdul Fadhil (Yayasan Al-Afif, 2025)
This study examines the application of Ukhuwah Islamiyyah values in Islamic education in Indonesia, referring to the thoughts of Nusantara scholars. Ukhuwah Islamiyyah is considered crucial to strengthen solidarity, tolerance, and brotherhood, particularly in the face of modernization and social pluralism. The study investigates how the concept of Ukhuwah Islamiyyah is integrated into the Islamic education curriculum and its impact on character building and social relations among students. It is expected that this research will contribute to the development of curricula that integrate ukhuwah values, ensuring that Islamic education in Indonesia focuses not only on academic aspects but also on the formation of moral and social character. The findings are hoped to offer new perspectives in strengthening the integration of ukhuwah values in the era of globalization.